Nonlinear Observer-Based Controller Design for VSC-Based HVDC Transmission Systems Under Uncertainties - Ilyass El Maysse; Abdelmounime El Magri; Aziz Watil; Abdulaziz Alkuhayli; Mohammed Kissaoui; Rachid Lajouad; Fouad Giri; Mohamed Metwally Mahmoud (IEEE Access, 2023)
This paper addresses the problem of output feedback control for high voltage direct current (HVDC) systems based on voltage source converters (VSC). Specifically, the system under study consists of two power grids and two VSC stations connected via a long HVDC cable. The primary goal of this paper is to propose a different approach for the online estimation of the grid voltage placed at a great distance from the control unit which is considered generally known, moreover the proposed technique aims to online estimation of the grid pulsation and the HVDC cable states, generally considered available. A nonlinear observer is intended to address these concerns. Only the line current measurements are used to estimate all state variables. Furthermore, utilizing the estimation offered by the proposed observer, an output feedback control strategy is formulated, using the backstepping design technique, to meet the three control objectives: 1) tight output voltage regulation of the HVDC cable; 2) ensuring a perfect power quality at both sides of the HVDC system; 3) regulation of the active power at the inverter station. The high effectiveness of the proposed output feedback controller’s performance is highlighted via a semi-experimental platform that includes a Processor In the Loop (PIL) on the embedded board eZdsp. Extra numerical simulations show that The proposed output feedback performance enjoys additional robustness properties and meets all control objectives.